Exploring Antecedents of Turnover Intention Among Generation Y Employees in Construction Industry - Neeta Syairul Amelia, Safian; Zaiton, Hassan; Mark, Kasa; Nur Fatihah, Abdullah Bandar; Nik Norsyamimi, Md Nor (Human Resource Management Academic Research Society, 2021)
Current reports claim that the constantly switching job became a norm among the Generation Y workforce in Malaysia with the reason being dissatisfied with the organization’s working system, pay and fringe benefits. This study aims to explore the antecedent leading to the Generation Y employees’ turnover intention. Five (5) Generation Y informants in construction industry were interviewed. Findings showed that generation Y employees prefer to stay at the current organization at least within five years. Antecedents of turnover intention identified are dissatisfaction towards the amount of wage received, a fringe benefits, access to better career opportunity or to change their career as well as family and/or personal reason. Retention factors identified include training and development, career development and good salary. Thus, to retain and motivate generation Y employees, organizations should implement proper human resource development programs such as training and career development while paying comparable salary and benefits. Keywords: Turnover Intention Antecedents, Generation Y, Malaysia.